Unraveling the role of NLRP3 inflammasome in allergic inflammation: implications for novel therapies - Lu, Hui-Fei; Zhou, Yi-Chi; Hu, Tian-Yong; Yang, Dun-Hui; Wang, Xi-Jia; Luo, Dan-Dan; Qiu, Shu-Qi; Cheng, Bao-Hui; Zeng, Xian-Hai (Frontiers in Immunology, 2024)
Allergic diseases like asthma, allergic rhinitis and dermatitis pose a significant global health burden, driving the search for novel therapies. The NLRP3 inflammasome, a key component of the innate immune system, is implicated in various inflammatory diseases. Upon exposure to allergens, NLRP3 undergoes a two-step activation process (priming and assembly) to form active inflammasomes. These inflammasomes trigger caspase-1 activation, leading to the cleavage of pro-inflammatory cytokines (IL-1β and IL-18) and GSDMD. This process induces pyroptosis and amplifies inflammation. Recent studies in humans and mice strongly suggest a link between the NLRP3 inflammasome, IL-1β, and IL-18, and the development of allergic diseases. However, further research is needed to fully understand NLRP3's specific mechanisms in allergies. This review aims to summarize the latest advances in NLRP3 activation and regulation. We will discuss small molecule drugs and natural products targeting NLRP3 as potential therapeutic strategies for allergic diseases.